2018
DOI: 10.4038/jas.v13i2.8338
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Maize Processors Towards Utilization of Maize Value Addition Techniques: Implications for Rural Entrepreneurship Development – A Study in Nigeria

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…The implication of the findings is that majority of the rural households in the study area have moderate size as against what used to be obtainable traditionally in most rural areas in Africa where parents with large household size use their children as cheap source of labour for their livelihood activities. This is similar to the findings of who reported that majority of rural community dwellers had a mean household size of 5 members (Alabi et al, 2018). Evidence from Table 1 also show that majority (86.5%) of the respondents were members of social organization while 13.5 percent did not belong to any social organization.…”
Section: Socio-economic Characteristicssupporting
confidence: 88%
“…The implication of the findings is that majority of the rural households in the study area have moderate size as against what used to be obtainable traditionally in most rural areas in Africa where parents with large household size use their children as cheap source of labour for their livelihood activities. This is similar to the findings of who reported that majority of rural community dwellers had a mean household size of 5 members (Alabi et al, 2018). Evidence from Table 1 also show that majority (86.5%) of the respondents were members of social organization while 13.5 percent did not belong to any social organization.…”
Section: Socio-economic Characteristicssupporting
confidence: 88%
“…In the sampled population, 76% of agripreneurs were using any type of labor they could obtain and afford. Most of them (70%) use family labour as a mean to cut down the excessive cost of production (Alabi et al, 2018). Though, the sample was biased towards female entrepreneurs, participation of female family labour (77%) and use of female labour hours ( 281 12 to 18 years 12 More than 18 years 2 significantly higher than participation of male family labour (33%) and use of male labour hours (119 hours) (Table 2).…”
Section: Profile Of Floriculture Entrepreneursmentioning
confidence: 99%